Optimizing adaptability and rational control strategies for cyclogyro systems - Sibei Wei (Авіаційно-космічна техніка та технологія)
The cyclogyro, due to its potential applications in aviation and complex dynamic characteristics, has become the focus of our research. Although traditional PID control is effective in many cases, it may struggle in handling the complex nonlinear dynamics often encountered in cyclogyro systems. Therefore, the objective of this study was to design and implement a control system for the cyclogyro based on optimized strategies to improve the system stability and response speed. The proposed approach integrates mathematical modeling, optimization algorithms, real-time data analysis, and feedback mechanisms to predict and adjust the system behavior. The performance of traditional PID control was compared with that of Model Predictive Control (MPC) in a dual-target speed control system. The numerical simulation results demonstrated that the MPC-based optimized control significantly outperformed PID control, achieving higher stability and faster response speed when dealing with external disturbances and nonlinear dynamic changes, with the average response time reduced by 92.5% (p < 1e-10). This enhanced performance is due to the system’s ability to dynamically adjust its control strategies in response to varying environmental conditions. The conclusions of this research highlight the substantial advantages of optimized control strategies for cyclogyro systems, offering new insights into the development of complex aviation control systems and demonstrating the potential of these strategies to enhance both performance and adaptability.